Cortical Matrix Mineral Density Measured Noninvasively in Pre‐ and Postmenopausal Women and a Woman With Vitamin D–Dependent Rickets. (7th June 2018) - Chiang, Cherie Y; Zebaze, Roger; Wang, Xiao‐Fang; Ghasem‐Zadeh, Ali; Zajac, Jeffrey D; Seeman, Ego
ABSTRACT: Reduced bone mineral density (BMD) may be due to reduced mineralized bone matrix volume, incomplete secondary mineralization, or reduced primary mineralization. Because bone biopsy is invasive, we hypothesized that noninvasive image acquisition at high resolution can accurately quantify matrix mineral density (MMD). Quantification of MMD was confined to voxels attenuation photons above 80% of that produced by fully mineralized bone matrix because attenuation at this level is due to variation in mineralization, not porosity. To assess accuracy, 9 cadaveric distal radii were imaged at a voxel size of 82 microns using high‐resolution peripheral quantitative computed tomography (HR‐pQCT; XtremeCT, Scanco Medical AG, Bruttisellen, Switzerland) and compared with VivaCT 40 (µCT) at 19‐micron voxel size. Associations between MMD and porosity were studied in 94 healthy vitamin D–replete premenopausal women, 77 postmenopausal women, and in a 27‐year‐old woman with vitamin D–dependent rickets (VDDR). Microstructure and MMD were quantified using StrAx (StraxCorp, Melbourne, Australia). MMD measured by HR‐pQCT and µCT correlated (R = 0.87; p  < 0.0001). The precision error for MMD was 2.43%. Cortical porosity and MMD were associated with age (r 2  = 0.5 and –0.4, respectively) and correlated inversely in pre‐ and postmenopausal women (both r 2  = 0.9, all p  < 0.001). Porosity was higher, and MMD was lower, in post‐ than in premenopausal women (porosity 40.3% ± 7.0 versus 34.7% ± 3.5, respectively; MMD 65.4% ± 1.8 versus 66.6% ± 1.4, respectively, both p < 0.001). In the woman with VDDR, MMD was 5.6 SD lower and porosity was 5.6 SD higher than the respective trait means in premenopausal women. BMD was reduced ( Z ‐scores femoral neck –4.3 SD, lumbar spine –3.8 SD). Low‐radiation HR‐pQCT may facilitate noninvasive quantification of bone's MMD and microstructure in health, disease, and during treatment. © 2018 American Society for Bone and Mineral Research.